Issues in Domestic Petroleum Pricing in Oil-Producing Countries - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2002)
This paper discusses issues relating to the domestic pricing of petroleum in oil-producing countries. It finds that in most major oil-exporting countries, government policies keep domestic prices below free-market levels, resulting in implicit subsidies that equaled 3.0 percent of GDP, on average, in 1999. Moreover, the paper argues, these petroleum subsidies are inefficient and inequitable-entailing substantial opportunity costs in terms of forgone revenue or productive spending-and also procyclical, complicating macroeconomic management. Nonetheless, the elimination of petroleum subsidies is often politically difficult, although countervailing measures and publicity campaigns can help engender support for reform.